Review on the Dispute Board Members’ Activity in Construction Business in Brazil - Quintão, Heider; Dias, Murillo (European Journal of Applied Sciences, 2024)
This article presents a comprehensive literature review on the current epistemology of Dispute Board (DB) Member activity in Brazil. The study identified in recent research key factors influencing DB activity, one of the Adequate Dispute Resolution (ADR) Methods, such as Negotiation, Mediation, Conciliation, Adjudication, and, Arbitration, as option to Litigation. This research provides valuable insights for improving Dispute Boards and advocating for regulatory changes, ultimately supporting best practices in value creation across various business scenarios and laying the groundwork for future research.